2014
DOI: 10.1371/journal.pone.0113067
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Cardiac Sarcomere Changes in a Rabbit Model of Intrauterine Growth Restriction

Abstract: BackgroundIntrauterine growth restriction (IUGR) induces fetal cardiac remodelling and dysfunction, which persists postnatally and may explain the link between low birth weight and increased cardiovascular mortality in adulthood. However, the cellular and molecular bases for these changes are still not well understood. We tested the hypothesis that IUGR is associated with structural and functional gene expression changes in the fetal sarcomere cytoarchitecture, which remain present in adulthood.Methods and Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
2
18
0
1
Order By: Relevance
“…We speculate that chronic hypoxia in utero resulted in longitudinal dysfunction because decreased longitudinal movement is mediated by subendocardial and subepicardial fibers, which are highly sensitive to hypoxia. 21 The observed significant increase in heart rate in the severe SGA group that was associated with decreased LS may represent a compensatory mechanism that preserves LV output. Crispi et al have presented similar findings in children (average age, 5 years) with a history of IUGR.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We speculate that chronic hypoxia in utero resulted in longitudinal dysfunction because decreased longitudinal movement is mediated by subendocardial and subepicardial fibers, which are highly sensitive to hypoxia. 21 The observed significant increase in heart rate in the severe SGA group that was associated with decreased LS may represent a compensatory mechanism that preserves LV output. Crispi et al have presented similar findings in children (average age, 5 years) with a history of IUGR.…”
Section: Discussionmentioning
confidence: 89%
“…7 An experimental study using an IUGR rabbit model has shown that chronic hypoxia in utero results in sarcomere shortening. 21 Those authors speculated that the shortened sarcomere might change the titin isoform, because titin is a large protein that determines sarcomere length. Interestingly, cardiac samples from human IUGR fetus autopsies have also demonstrated shorter sarcomeres.…”
Section: Systolic Functionmentioning
confidence: 99%
“…There were also changes in the heart and kidneys in rabbit kits in response to surgical ligature of uteroplacental vessels. In particular, reduced uteroplacental blood flow decreased fetal heart weight and caused systolic and diastolic dysfunction (Schipke et al, ) in association with an increase in myocardial wall thickness, left ventricular hypovascularisation and hypertrophy, altered expression of metabolic genes, and disorganized cardiomyocyte ultrastructure (reduced sarcomere length and mitochondrial density; Gonzalez‐Tendero et al, ; Guitart‐Mampel et al, ; Gumus et al, ; Schipke et al, ; Torre et al, ). Utero‐placental insufficiency also reduced kidney weight, decreased renal glomeruli number and lead to glomerular capillary congestion and oxidative stress in developing rabbits kits (Bassan et al, ; Figueroa et al, ).…”
Section: Models Of Iugr and Fetal Programmingmentioning
confidence: 99%
“…Previously, using the same animal model, Gratacós described that fetal echocardiography showed a more globular cardiac shape, with a lower right sphericity index but similar wall thickness, in UCR subjects compared with that in controls. Furthermore, the control and UCR groups showed similar ejection fractions, although the UCR group had lower mitral annular peak velocities (S′), suggesting cardiac dysfunction . Using our model of IUGR, we found a similar wall thickness in UCR rabbits as in controls, but we did not test mitral annular peak velocities.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, the control and UCR groups showed similar ejection fractions, although the UCR group had lower mitral annular peak velocities (S 0 ), suggesting cardiac dysfunction. 16 Using our model of IUGR, we found a similar wall thickness in UCR rabbits as in controls, but we did not test mitral annular peak velocities.…”
Section: Discussionmentioning
confidence: 72%